World Economy Autumn 2024: Momentum remains weak - Klaus-Jürgen Gern; Stefan Kooths; Jan Reents; Nils Sonnenberg (Kiel Institute for the World Economy (IfW Kiel), 2024)
The global economy continues to expand at a moderate pace. The somewhat faster pace in the spring appears to have slowed again in the summer. In the United States, the economy is gradually losing momentum. At the same time, economic momentum in Europe remains low and a sustained economic recovery in China is still not in sight. Although world trade in goods has risen again in the course of the year to date, trade momentum remains week amid signs that global manufacturing production is currently slowing down again. Monetary policy is still restrictive for the time being, but a turnaround in interest rates has been initiated and tailwinds from more favorable financing conditions will increasingly support economic going forward. Against this backdrop, global economic expansion is likely to continue this year and next at an almost unchanged, moderate pace, with private consumption in Europe in particular strengthening amid rising real wages. We expect global output - measured on the basis of purchasing power parity - to increase by 3.2 percent this year. Next year, growth will be slightly lower at 3.1 percent. We have thus left our expectations unchanged compared to our summer forecast for this year and revised them slightly downwards - by 0.1 percentage points - for 2025. For 2026, we expect a gradual acceleration and growth of 3.3 percent. Although unemployment in the advanced economies will rise slightly this year and next, it will remain at historically low levels. The decline in inflation has been slow of late, mainly due to the persistent rise in prices for services and the fact that energy prices are no longer falling year-on-year. The expected further decline towards the target of 2 percent is likely to be slow, and there remains a risk that monetary policy will have to remain restrictive for longer than currently expected. Further risks for the global economy lie in a possible escalation of geopolitical conflicts and arise from the uncertainties in connection with the US presidential elections. In particular, intensified trade disputes would have a negative impact on global economic activity.
Keywords: 330; Europe; USA; Emerging Markets & Developing Countries; Welfare State; Business Cycle World